Do We – and Should We – Have a Canadian Bioethics? - Racine, Eric (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
Do we have a genuinely Canadian bioethics – and not only a practice of bioethics in Canada? This question, and this paper, are about the connection between bioethics and the actual healthcare, research, and public health experiences of Canadians. In addressing it, I am inspired by the philosophy of pragmatism that stresses the importance of everyday experience as a starting point for ethics, and of human flourishing as a goal for ethics. Through this lens, an ideal Canadian bioethics is one that is rooted in the lived experiences of Canadians; it reflects the ideal of flourishing projected by Canadian individuals, including their views on their political communities. However, it is unclear if a full-fledged Canadian bioethics has taken shape given increasingly uniform scholarship worldwide that sets expectations about the kinds of moral problems worth investigating and the kinds of solutions to be adopted. In the spirit of thinking about this question, I discuss aspects of Canadian society that could shape the development of a Canadian bioethics: (a) the existence of competing Canadian political narratives, (b) the distinctiveness of Canadian healthcare systems and healthcare experiences, (c) the commitment of Canadians to certain values and aspirations, (d) the institutional and procedural aspects of the Canadian public sphere, (e) the challenges of increasingly uniform scholarship across geographic and national contexts, and (f) the practical obstacles to developing a Canadian bioethics. These challenges that Canadian bioethics faces are likely relevant internationally for all contexts in which socially shaped moral problems are discussed and solutions envisioned.